Espécies de Scarabaeinae (Coleoptera: Scarabaeidae) de fragmentos florestais com diferentes níveis de alteração em Santa Maria, Rio Grande do Sul - Silva, Pedro Giovâni da (2011)
This study aims to contribute to the scarce data on the Scarabaeinae fauna of the Rio Grande do Sul, Brazil. Twenty-four samplings were made with pitfall traps baited with human excrement, rotting meat and fermented banana in three forest fragments with different degrees of disturbance in Santa Maria, RS, between May 2009 and April 2010, in order to investigate the diversity of Scarabaeinae in these habitats and learn about the feeding preference in relation to the baits used and the temporal distribution of species. A total of 19,699 individuals of 33 species were collected. The greatest richness of Scarabaeinae was found in a forest fragment with larger size and highest conservation level, whereas the greatest abundance occurred in a forest fragment with intermediate level of perturbation. The spring, then summer, was the greatest period of richness and abundance of Scarabaeinae. The richness and abundance were positively correlated with temperature during the study period. Human excrement was the most attractive bait in number of species and individuals. Aiming to help the future identification of studied species is presented a local identification guide containing an illustrated dichotomous key, ecological information and illustrations of species of Scarabaeinae cited to Santa Maria. Through an extensive literature review was possible to provide a preliminary list, even nonexistent, of genera and species of Scarabaeinae cited for Rio Grande do Sul. Widen the distribution of Sulcophanaeus rhadamanthus (Harold, 1875) to Rio Grande do Sul, being a recent record of the same, where it was not captured nearly 80 years.